Megiddo Microgeoarchaeology in the Field and in the Lab - Shahack-Gross, Ruth (Near Eastern archaeology, 2025)
Micro-geoarchaeological research at Tel Megiddo targets questions about construction materials, occupation deposits in domestic and public sectors of the city, destruction, abandonment, and postdepositional processes. Since 2006, employing primarily the methods of micromorphology, infrared spectroscopy, phytolith, dung spherulite, and wood ash analysis, significant insights have been gained. This article presents three case studies that show the strength of micro-geoarchaeology for obtaining a general understanding of the history and archaeology of Megiddo’s inhabitants: (1) characterization of domestic trash deposits, (2) characterization of construction materials and the implications for understanding the natural resources that were used by the site’s inhabitants, and (3) understanding the mechanism and processes that took place during Megiddo’s most famous destruction by fire.